Infrared microspectroscopy of plants: use of synchrotron radiation infrared microspectroscopy to study plant root anatomy and to monitor the fate of organic contaminants in those roots - Dokken, Kenneth M. (Kansas State University, 2006)
The fate and bioavailability of organic contaminants in plants is a major ecological and human health concern. Current wet chemistry techniques that employ strong chemical treatments and extractions with volatile solvents, such as GC-MS, HPLC, and radiolabeling, although helpful, degrade plant tissue resulting in the loss of spatial distribution and the production of artifacts. Synchrotron radiation infrared microspectroscopy (SR-IMS) permits direct analysis of plant cell wall architecture at the cellular level in situ, combining spatially localized information and chemical information from the IR absorbances to produce a chemical map that can be linked to a particular morphology or functional group. This study demonstrated the use of SR-IMS to probe biopolymers such as cellulose, lignin, and proteins in the root tissue of hydroponically grown sunflower and maize plants as well as to determine the fate and effect of several organic contaminants in those root tissues. Principal components analysis (PCA), a data compression technique, was employed to reveal the major spectral variances between untreated and organic contaminant treated root tissues. Treatment with 1H-benzotriazole (BT) caused alterations to the lignin component in the root tissue of plants. The BT was found in xylem and epidermal tissue of sunflower plants but not associated with any particular tissue in maize roots. 2,4-dinitrotoluene (2,4-DNT) and 2,6-dinitrotoluene (2,6-DNT) altered the pectin and polysaccharide structure in both maize and sunflower. SR-IMS revealed the reduction of DNTs to their aromatic amine form in the vascular and epidermal tissues at low concentration. At high concentration, DNTs appeared to be associated with all the plant tissues in maize and sunflower. Exposure of sunflower and maize to 2,6-dichlorophenol (2,6-DCP) caused alterations to the polysaccharide and protein component of the root tissue. In some cases, phenolic compounds were observed in the epidermal tissue of maize and sunflower roots. The results of this research indicate that SR-IMS has the potential to become an important analytical tool for determining the fate and effect of organic contaminants in plants.
Keywords: Infrared Microspectroscopy; Synchrotron Radiation; Phytoremediation; Organic Contaminants; Sunflower; Maize; Agriculture, Agronomy (0285); Chemistry, Analytical (0486); Chemistry, Biochemistry (0487)